FAKTOR RESIKO KEJADIAN OSTOARTHRITIS LUTUT PADA PASIEN YANG BEROBAT DI POLI ORTOPEDI DI RUMAH SAKIT BHAYANGKARA TK. II MEDAN - Evi Melva Frida Manurung; Donal Nababan; Mido Ester J. Sitorus; Kesaktian Manurung; Evawani Martalena Silitonga (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The specific purpose of this study was to determine the distribution of risk factors (age, gender, body mass index, family history, history of knee injury, hypertension, diabetes mellitus, hypercholesterolemia, smoking, occupation and physical activity) in knee joint OA patients at the Orthopedic Home Clinic. Sick Bhayangkara TK. II Medan from February to June 2022. This study used an observational analytic method with a cross sectional study design. The study was carried out from February to August 2022. The population of this study were knee osteoarthritis patients who were treated at the Orthopedic Poly, Bhayangkara TK Hospital. II Medan totaled 127 people. The sample of this study was knee OA patients with inclusion criteria and willing to be included in the study. Sampling was done by purposive sampling. The number of samples obtained by the slovin formula was obtained as many as 56 respondents. The results of the bivariate analysis showed that there was a significant relationship between age and knee OA (p = 0.010), there was a relationship between gender and knee OA, there was a relationship between body mass index and knee OA (p = 0.027), there was a relationship between a history of knee injury and OA. knee, physical activity was p = 0.004 indicating that there was a relationship between physical activity and knee OA, there was no relationship between diabetes and knee OA (p = 0.279), there was no relationship between hypercholesterolemia and knee OA p = 0.107, there was no relationship between habit smoking with knee OA (p = 0.304), there is no significant relationship between work and knee OA p = 0.269. The results of multivariate analysis showed that the independent variables that influenced knee OA were age (p=0.015) and history of knee injury (p=0.001). The OR value for the age variable is 2.220, this indicates that the risk of knee OA in elderly patients (>45 years) is 2 times greater than in adolescent-adult patients (?45 years). While the OR value on the variable history of knee injury is 0.045. To the Community Further research is needed on other risk factors such as growth disorders (Perthes disease, CDH, CTEV) and multigravida, Further Research Further research is needed on risk factors and the degree of pain on the severity of knee OA based on radiological examination.